Experiences in Work Relationships: A Measure of Attachment Strategies at Work - Seitl, Martin; Charvát, Miroslav; Střelec, Jan; Seitlová, Klára; Kafetsios, Konstantinos (Psychological reports, 2023)
Much of the burgeoning research on adult attachment in organizational settings has utilized assessment methods developed for personal or social relationships contexts. Here, we propose and test a novel framework for assessing attachment orientations in the workplace, the Experiences in Work Relationships-Individual (EWR-I), based on a conceptualization of the regulatory functions of attachment dynamics. Using data from two samples comprising early career starters and employees in the Czech Republic (N = 588 and N = 633) analyses confirmed the bifactorial structure of the new scale corresponding to "interpersonal hyperactivation" (involving emotional instability, negative emotionality, and lack of appreciation in work relationships) and a second factor termed "interpersonal deactivation" (involving distancing from others and relationships at work, mistrust and inhibition of positive emotionality). Evidence of convergent and discriminant validity against general relational assessments of adult attachment, and predictive and construct validity against measures of workplace personality, organizational citizenship behavior and counterproductive work behavior further documented the nature and utility of the new scale. We argue that interpersonal hyperactivation and deactivation represent two distinct and measurable key components of attachment behavior dynamics at work.
Keywords: pracoviště; Personality Disorders; Object Attachment; Humans; personality assessment; poruchy osobnosti; emotion regulation; interpersonální vztahy; Workplace; dospělí; afektivní symptomy; lidé; attachment at work; připoutání k objektu; Adult; secondary attachment strategies; osobnost; Personality; Affective Symptoms; Interpersonal Relations